1996
DOI: 10.1016/0014-5793(96)00553-4
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of macrophage migration inhibitory factor from human Å lymphocyte at 2.1 Å resolution

Abstract: The three-dimensional structure of the macrophage migration inhibitory factor (MIF) from human lymphocytes has been determined by X-ray crystallography at 2.1 A resolution. The structure was solved by a molecular replacement technique using the coordinates of rat MIF. The molecule forms a trimer structure similar to the rat MIF. However, unlike the rat MIF whose C-terminal tail (residues 104-114) is disordered in the crystal, human MIF has a deftite main-chain conformation up to the C-terminal end. These eleve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
53
0
3

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 16 publications
4
53
0
3
Order By: Relevance
“…The N-terminal proline residue, which is the catalytic center of the isomerase activity of mammalian MIF (26), is conserved in XMIF. In mammalian MIF, a number of aromatic residues are clustered around this proline (27,28). These surrounding residues are all conserved in XMIF, suggesting their importance in the function or formation of the structure of MIF.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The N-terminal proline residue, which is the catalytic center of the isomerase activity of mammalian MIF (26), is conserved in XMIF. In mammalian MIF, a number of aromatic residues are clustered around this proline (27,28). These surrounding residues are all conserved in XMIF, suggesting their importance in the function or formation of the structure of MIF.…”
Section: Resultsmentioning
confidence: 99%
“…Residues conserved in all the proteins listed are boxed, including the N-terminal proline that is the catalytic center of the isomerase activity of MIF (26), and those conserved in mammalian MIF and XMIF are marked by a plus sign (ϩ). The asterisks represent the residues clustered around the N-terminal proline (27,28). The dollar sign ($) denotes the lysine residue, which has also been implicated in the enzymatic activity (29,30).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three-dimensional x-ray crystallographic studies have shown that human MIF exists as a homotrimer and is structurally related to the bacterial enzymes 4-oxalocrotonate tautomerase and 5-carboxymethyl-2-hydroxymuconate isomerase (25,26). MIF possesses the unusual ability to catalyze the tautomerization of the non-physiological substrates D-dopachrome and L-dopachrome methyl ester into their corresponding indole derivatives (27).…”
mentioning
confidence: 99%
“…MIF contains a CXXC TPOR consensus motif, with the residues Ala and Leu placed between the cysteines and also contains additional conserved residues that are frequently found N-terminally of the CXXC region (16). Although the overall three-dimensional structure of the MIF monomer shows a remote resemblance to the Trx monomer, MIF is not structurally homologous to the TPOR proteins, and the Cys-Ala-Leu-Cys (CALC) redox motif of MIF lies at the N terminus of a ␤-strand element with Cys 57 located in the preceding loop (17,18) rather than in a Trx-like fold. MIF exhibits TPOR activity in vitro being able to catalyze the reduction of both insulin and small molecular weight compound disulfides (19 -21).…”
mentioning
confidence: 99%